Antioxidant Potential Of Ethanol Extract Of Kendondong Leaves (Spondias Dulcis), Characterization And Examination Of Quercetin By TLC Method - Cahya, Cucu Arum Dwi; Harahap, Urip; Nasution, M. Pandapotan (Publisher Cv. Inara, 2023)
Indonesia has a variety of plants that can be used to cure various diseases. Natural therapies offer little negative effect, especially in degenerative diseases, due to decreased function of body cells damaged by oxidation. Antioxidants have a vital role in counteracting free radicals to prevent degenerative diseases. One of the most abundant sources of antioxidant compounds is flavonoids. Kedondong leaf (Spondias dulcis) is one of the plants which is also suspected to contain flavonoids. Spondias species contain triterpenoids, namely oleanolic acid and flavonoids such as quercetin, kaempferol, kaempferida and rhamnetin. Examination of simplicia characteristics, phytochemical screening, examination of quercetin with Thin Layer Chromatography, and determination of antioxidant activity and IC50 value of Kedondong leaves using the DPPH method were carried out in this study. The results of the characteristic examination showed that simplicia met the requirements with a water content of 8.63%, a water-soluble extract content of 19.42%, an ethanol-soluble extract content of 5.17%, a total ash content of 12.43%, an acid-insoluble ash content of 7 .81%. Phytochemical screening showed that the bright kedondong leaves contained flavonoids, alkaloids, glycosides, saponins, tannins, and steroids/triterpenes. Examination of quercetin thin layer chromatography with chloroform: methanol (70: 30) as eluent produced six stains with Rf values (0.5; 1; 1.2; 3; 4.3; 6.6), and compared with quercetin raw material on the sixth stain with an Rf value of 6.6 has the same stain as the ethanol extract of kendondong leaves. The results of antioxidant testing at a 400 – 800 nm wavelength using UV-Vis spectrophotometry obtained a maximum wavelength of 515 nm. IC50 value obtained an IC50 value of 68.6260 ppm, so it can be concluded that the ethanol extract of kendondong leaves has antioxidant activity in the strong category.